2015
DOI: 10.1097/cji.0000000000000059
|View full text |Cite
|
Sign up to set email alerts
|

Ex Vivo–expanded Natural Killer Cells Demonstrate Robust Proliferation In Vivo in High-risk Relapsed Multiple Myeloma Patients

Abstract: Highly activated/expanded natural killer (NK) cells can be generated via stimulation with the HLA-deficient cell line K562 genetically modified to express 41BB-ligand and membrane-bound interleukin (IL)15. We tested the safety, persistence and activity of expanded NK cells generated from myeloma patients (auto-NK) or haplo-identical family donors (allo-NK) in heavily pretreated patients with high-risk relapsing myeloma. The preparative regimen comprised bortezomib only or bortezomib and immunosuppression with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
134
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(142 citation statements)
references
References 43 publications
6
134
1
1
Order By: Relevance
“…The use of fresh versus cryopreserved cells is likely due to observed poor post-thaw viability and functionality of NK cells [49,50,58,59]. In one study directly comparing fresh NK cells and NK cells that had been frozen, thawed and re-cultured, it was shown that the cryopreserved cells did not show proliferation in the patients who received the cellular therapy [50]. It is noteworthy that cryopreserved NK cells were shown to have fair viability (70%) but poor cytotoxicity after thawing [60].…”
Section: Cryopreserved Nk Cells In Clinical Trialsmentioning
confidence: 99%
“…The use of fresh versus cryopreserved cells is likely due to observed poor post-thaw viability and functionality of NK cells [49,50,58,59]. In one study directly comparing fresh NK cells and NK cells that had been frozen, thawed and re-cultured, it was shown that the cryopreserved cells did not show proliferation in the patients who received the cellular therapy [50]. It is noteworthy that cryopreserved NK cells were shown to have fair viability (70%) but poor cytotoxicity after thawing [60].…”
Section: Cryopreserved Nk Cells In Clinical Trialsmentioning
confidence: 99%
“…Up to now, clinical NK cell doses can be reached even up to 10 8 NK cells/kg [165]. However, there are numerous factors that may affect the effector function of expanded NK cells.…”
Section: Adoptive Transfer Of Donor Natural Killer Cells and Natural mentioning
confidence: 99%
“…Expansion, and activation of human NK cells ex vivo has been demonstrated in the presence of human leukocyte antigen (HLA) deficient cell line K562 genetically modified to express an activated T-Cell ligand (41BBL) and interleukin-15 (IL-15.) Safe auto- or allo-transplant of educated NK cells has been demonstrated in patients [106]. Similarly to T-cells, CAR-NK cells are also under investigation for the treatment of myeloma, with CS1 as a potential therapeutic target [107].…”
Section: The Impact Of Hematopoietic Derived Cells On Myeloma Progresmentioning
confidence: 99%